Development of the Secretariat Information System and Membership of the Tapak Suci Putera Muhammadiyah Using E-R Diagrams - Tirkaamiasa, Taufik; Sofianti, Evin (Formosa Journal of Computer and Information Science, 2024)
Tapak Suci Putera Muhammadiyah has become one of the original martial arts schools in Indonesia that has become global. On the other hand, the globalization of information and communication is developing so rapidly that it is not supported by the optimal use of technology. The purpose of this study is to analyze the optimal triggers for the use of information technology for the development of the Tapak Suci Putera Muhammadiyah organization. This study uses a qualitative method with data collection techniques through interviews, observations, and literature studies. The analysis method using ERD (Entity Relationship Diagram) will form an information database. This research results that the information system on the official website to build the secretariat and membership of Tapak Suci by using the database resulting from the transformation of the E-R diagram will be faster, easier, and expected in accordance with the needs and expectations of users in getting clearer information